Chemoselective Three-Component Coupling via A Tandem Pd Catalyzed Boron-Heck and Suzuki Reaction - O’Neill, Justin (2008)
Reported herein is a new approach to prepare biaryl derivatives via a tandem Pd catalyzed boron-Heck and Suzuki reaction. This one-pot tandem process avoided purification or addition of extra catalyst between steps. The resulting biaryl compounds can be prepared with substrate variability in good to moderate yields.